Expression and clinical significance of focal adhesion kinase and adrenomedullin in epithelial ovarian cancer - LI, MINGQUN (Oncol Lett, 2015)
The aim of the present study was to investigate the expression of focal adhesion kinase (FAK) and adrenomedullin (ADM) and determine their clinical significance and cooperative role in human epithelial ovarian cancer. The expression of FAK and ADM was investigated in epithelial ovarian cancer, benign ovarian tumors and normal control tissues by immunohistochemical staining and optical microscopy. The FAK and ADM expression and correlation with clinicopathological parameters was analyzed using SPSS 13.0 software. The expression of FAK and ADM in epithelial ovarian cancer was significantly higher compared with that in benign tumors or normal ovarian tissues (P<0.01); however, no significant difference was observed between benign tumors and normal tissues (P>0.05). The expression of FAK was found to be correlated with histological grade, clinical stage, lymph node metastasis and prognosis (P<0.05), but exhibited no significant association with patient age or histological type (P>0.05). The expression of ADM was significantly correlated with pathological grade, lymph node metastasis and prognosis (P<0.05), but not with age, clinical stage or histological type (P>0.05). The Spearman's rank correlation analysis revealed a positive correlation between FAK and ADM expression (r=0.314). FAK and ADM were more highly expressed in epithelial ovarian cancer compared with benign tumors or normal ovarian tissues. Furthermore, FAK and ADM may play a cooperative role; specifically, FAK may upregulate ADM in the invasion and migration of epithelial ovarian cancer. Thus, FAK and ADM may represent potential biomarkers for evaluating the malignant potential and prognosis of ovarian cancer.